2019
DOI: 10.1002/jcp.28877
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of zinc finger protein A20 as a suppressor of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC), the third leading cause of cancer-associated mortality worldwide, is a major public health problem. Zinc finger protein A20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Among all of the upregulated genes, several stand out as possible mediators of entolimod's tissue protective activity in the liver. For example, the tissue protective TNFAIP3 (A20) protein was previously shown to specifically reduce TNF toxicity and protect the liver and endothelial cells from apoptosis [50,51] and was strongly induced by entolimod in both our liver and hepatocyte experiments (10.42-fold and 7.15-fold, respectively), but was not upregulated in livers after LPS treatment. Another gene found to be strongly upregulated by entolimod in our study is RCAN1 (regulator of calcineurin 1), which was previously shown to preserve endothelial integrity and reduce vascular barrier breakdown by increasing resistance to damaging systemic anaphylaxis [52].…”
Section: Pro-survival Transcriptional Response To Entolimod In the Mumentioning
confidence: 79%
“…Among all of the upregulated genes, several stand out as possible mediators of entolimod's tissue protective activity in the liver. For example, the tissue protective TNFAIP3 (A20) protein was previously shown to specifically reduce TNF toxicity and protect the liver and endothelial cells from apoptosis [50,51] and was strongly induced by entolimod in both our liver and hepatocyte experiments (10.42-fold and 7.15-fold, respectively), but was not upregulated in livers after LPS treatment. Another gene found to be strongly upregulated by entolimod in our study is RCAN1 (regulator of calcineurin 1), which was previously shown to preserve endothelial integrity and reduce vascular barrier breakdown by increasing resistance to damaging systemic anaphylaxis [52].…”
Section: Pro-survival Transcriptional Response To Entolimod In the Mumentioning
confidence: 79%
“…Our results highlight the important role of proinflammatory mechanism mediated by RIPK1 in promoting liver fibrosis and HCC formation, largely independent of cell death and compensatory proliferation. In this regard, it is interesting to note that down-regulation of A20, an important suppressor of RIPK1 and the NF-κB pathway, has been associated with invasiveness of human HCCs and reduced disease-free survival (62). Mutant mice with A20 knockout specifically in liver parenchymal cells spontaneously develop chronic liver inflammation but no fibrosis or HCCs (63).…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of TNFAIP3 was also found in pancreatic cancer tissues 35 . Studies on liver tumor development indicated that TNFAIP3 plays an important role in liver protection and tumor prevention, by limiting chronic liver in ammation, stimulating hepatocyte growth, inhibiting the activation of protein tyrosine kinase 2 and Rac family GTPase 1, and preventing epithelial-mesenchymal transition 36,37 . Based on the expression pro le analysis of TNFAIP3 in TCGA database and lung tumor tissue microarray, we hypothesized that TNFAIP3 plays the role of tumor suppressor in lung tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%